Mortuary Practices in the Persian Period of the Levant - Wolff, Samuel Richard 1950- (2002)
The Persian period (586-332 BCE) in the southern Levant saw the presence of Greeks, Cypriots, Phoenicians and Persians on Levantine soil, mixing with the local inhabitants, many of whom had only recently returned from exile. This mix of cultures can be traced through the mortuary remains, which the author surveys here, looking in particular at the location of tombs relative to settlements, tomb typology and orientation, the position of the body, and the analysis of skeletal remains and grave goods.